Variables associated with low, moderate and high emergency department use among patients with substance-related disorders. (1st February 2020) - Penzenstadler, Louise; Gentil, Lia; Huỳnh, Christophe; Grenier, Guy; Fleury, Marie-Josée
Highlights: ED use was common among individuals with substance-related disorders (SRD). High ED users with SRD presented more complex and severe conditions. High ED users mostly visited for subacute or non-urgent problems. Moderate users had more alcohol-induced disorders and acute common mental disorders. Moderate ED users mostly visited for non-urgent care. Abstract: Aims: This study identified factors associated with frequency of emergency department (ED) use for medical reasons among patients with substance-related disorders (SRD) in Quebec (Canada) for 2014–15. Methods: Participants (n = 4731) were categorized as: 1) low (1 visit/year), 2) moderate (2 visits/year), and 3) high (3+ visits/year) ED users. Independent variables included predisposing, enabling and needs factors based on the Andersen Behavioral Model. Multinomial logistic regression identified associated variables. Results: Factors positively associated with moderate and high ED use included adjustment disorders, suicidal behavior, alcohol-induced disorders, less urgent to non-urgent illness acuity, referral to local health community services centers (LHCSC) at discharge, and living in a materially deprived area. Factors positively associated with high ED use only included anxiety disorders, alcohol use disorders, drug use disorders, chronic physical illness, subacute problems, prior ED use for MD and/or SRD, prior LHCSC medical interventions, physician consultation within one month after discharge, living in very deprived or middle-class areas, and, negatively, being hospitalized for medical reasons in second ED visit. Moderate ED use only was negatively associated with alcohol intoxication and being referred to a GP at ED discharge. Conclusions: Compared to low ED users, most high users with SRD were men presenting more complex and severe conditions. They visited ED mainly for subacute or non-urgent problems. Compared to low ED users, most moderate users had alcohol-induced disorders, less alcohol intoxication, and acute common MD. They visited ED mainly for non-urgent care. Diverse strategies should be implemented to reduce ED visits, targeting each group.